Reproductive phenology of Polygonum hispidum Kunth and P. punctatum Elliott (Polygonaceae), in response to the flooding cycle in the Pantanal, Brazil - Catian, Gisele; Scremin-Dias, Edna; Pott, Arnildo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
In flood-driven environments the life cycles of organisms are regulated in function of the water regime. The objective of this work is to analyse the phenophases of flowering and fructification of two species of amphibious aquatic macrophytes, Polygonum hispidum Kunth and P. punctatum Elliott, with regard to the flooding cycle of the Brazilian Pantanal. We collected monthly data in 26 plots of 20 ponds during two years. The flooding phases were classified as drought, rising, flood, and receding. The periods with an abundance of water (rising, flooding, and receding) were the most important for reproduction. Both species bear fruits at flood, when the water is deepest and remains until receding, and most seeds are dispersed. The synchrony between reproductive cycles and these flood phases suggests the importance of seasonality in the reproductive patterns of these species.